The comparison of nail and serum trace elements in patients with epilepsy and healthy subjects - Ilhan, A; Özerol, E; Güleç, M; Isik, B; Ilhan, N; Ilhan, N; Akyol, Ö (Pergamon-Elsevier Science Ltd, 2004)
The objective of this prospective study was to determine the levels of manganese (Mn), copper (Cu), and zinc (Zn) levels in both nail and serum from patients with epilepsy. For this purpose, levels of these elements were measured in 31 patients with epilepsy and 19 healthy subjects. Element analyses were carried out by atomic absorption spectrophotometer (AAS). Increased Mn levels were detected in nail of patients with epilepsy compared to healthy controls (P<.008). The main nail Zn and Cu levels were found to be unchanged in epileptic patients compared to control subjects. There were no significant differences in serum Mn and Zn levels between epileptic patients and control subjects. However, there was a statistically significant increase in serum Cu levels in patients with epilepsy in comparison with control group (P<.009). Our results demonstrate that some trace element levels may vary in epileptic patients, and because of the more stable status, the analysis of these element levels in some tissues such as nail might be superior to serum analysis. (C) 2003 Elsevier Inc. All rights reserved.
Keywords: epilepsy; nail; serum; copper; zinc; manganese